Strategically Selecting Behaviors That Impact the Problem: An Approach Drawn from Social Marketing - Laura A. Sanagorski Warner; John M. Diaz (EDIS)
Extension professionals and other practitioners address a wide variety of complex issues by providing education and encouraging behavior change using innovative strategies. The importance of prioritizing potential behaviors and selecting those with high expected impact cannot be overemphasized. However, behavior selection can be complicated because there are many solutions for any problem in a particular context. Using an approach drawn from social marketing to develop activities aimed at changing or maintaining people’s behavior, Extension professionals and other practitioners can prioritize behaviors by mathematically calculating anticipated weights that will help focus efforts around key behaviors with the potential to make the greatest impact. This new 6-page publication of the UF/IFAS Department of Agricultural Education and Communication provides an overview of a process to collect and analyze the impact and the likelihood of adoption to help Extension professionals decide on behaviors for a campaign or intervention. Written by Laura A. Warner and John M. Diaz. https://edis.ifas.ufl.edu/wc375